Pengaruh Current Ratio (CR) dan Return On Asset (ROA) terhadap Harga Saham pada PT Gudang Garam Tbk Periode 2014 – 2023 - Simangunsong, Ria Rosalia; Kusmawati, Yeti; Karmiyati, Sari (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Stock prices are a crucial indicator of a company's financial performance and market perception, particularly for investors in capital markets. This study investigates the influence of Current Ratio (CR) and Return on Assets (ROA) on the stock price of PT Gudang Garam Tbk during the 2014–2023 period. Understanding these relationships is essential for investors and stakeholders to make informed decisions based on financial indicators. Employing a quantitative research approach, this study utilizes descriptive methods and multiple linear regression analysis. Financial data were drawn from the company’s Balance Sheets and Income Statements over a ten-year span, and data analysis was conducted using SPSS 26. The findings reveal that CR, as a liquidity indicator, does not have a significant impact on stock price, suggesting that short-term financial health may not directly influence investor valuation in this case. In contrast, ROA shows a significant effect on stock price, indicating that profitability is a critical factor for market valuation. When tested together, both CR and ROA have a collective influence on stock price performance. The determination coefficient reveals that over half of the stock price variability can be explained by these two financial ratios, underscoring their relevance, while the remainder is likely influenced by external or unobserved factors.